Quantization of rotating linear dilaton black holes - Sakallı, İzzet (European Physical Journal C, Springer, 2015)
In this paper, we focus on the quantization of 4−dimensional rotating linear dilaton black hole (RLDBH) spacetime describing an action, which emerges in the Einstein-Maxwell-Dilaton-Axion (EMDA) theory. RLDBH spacetime has a non-asymptotically flat (NAF) geometry. When the rotation parameter " a" vanishes, the spacetime reduces to its static form, the so-called linear dilaton black hole (LDBH) metric. Under scalar perturbations, we show that the radial equation reduces to a hypergeometric differential equation. Using the boundary conditions of the quasinormal modes (QNMs), we compute the associated complex frequencies of the QNMs. In a particular case, QNMs are applied in the rotational adiabatic invariant quantity, and we obtain the quantum entropy/area spectra of the RLDBH. Both spectra are found to be discrete and equidistant, and independent of a−parameter despite the modulation of QNMs by this parameter.
The file in this item is the publisher version (published version) of the article.
Keywords: Quantization; rotating linear dilaton black holes; general relativity; black holes; quasinormal mode